The Influence of Non-performing Financing and Financing To Deposit Ratio on Profitability in Sharia Commercial Banks in Indonesia - Lubis, Dody Suhanda; Hilmi; Hismendi, (International Journal of Scientific Research and Management (IJSRM), 2024)
Islamic banks must also play an active role in building dynamics in society, one of which is financial profitability (ROA) and Non-performing Financing (NPF). Return on Assets (ROA) is a company's financial ratio that is related to profitability, measuring the company's ability to generate profits. Furthermore, if the NPF value of sharia banking decreases, it will increase the performance of sharia banks. This research aims to determine the effect of Non Performing Financing (NPF) and Financing To Deposit Ratio (FDR) on profitability at Sharia Commercial Banks in Indonesia. Panel data regression analysis is regression analysis based on panel data to observe the relationship between the dependent variable and the independent variable. The analytical method used in this research is the panel data analysis method using the classical assumption test (Ordinary Least Square) with the aim of carrying out the classical assumption test so that the estimator parameter values ​​are valid and unbiased. The research results found that NPF partially had no effect on the profitability of Sharia Commercial Banks in Indonesia, while FDR partially had an effect on the profitability of Sharia Commercial Banks in Indonesia.